Two new cane-like species of Begonia L. (Begoniaceae) from central Vietnam - Shui, Yu-Min; Vu, Chinh Tien; Le, Tuan Anh; Pham, Thi Thanh Dat; Nguyen, van Dat; Duong, Thi Minh Hoang; Lei, Li-Gong (Phytotaxa, 2019)
Two new cane-like species of Begonia from central Vietnam, Begonia bachmaensis and B. saolaensis, are described and illustrated. Begonia bachmaensis is similar to B. boisiana and does not fit within any of the current sections. Begonia saolaensis is similar to B. rubrosetosa and is assigned to Begonia sect. Petermannia. Begonia bachmaensis is classified as Data Deficient (DD) and B. saolaensis is assigned in the Endangered (EN) category according to IUCN criteria.